RIGHT TO INTERNET ACCESS AS A MEANS OF ENSURING A DECENT LIFE - Rzayeva Gulnaz Aydin,; Rahimova Malakkhanim Seyfulla, (International Journal of Innovative Technologies in Social Science, 2025)
The rights of people to a decent life, which is a supreme goal in the constitutions of most countries of the world, are also reflected in many international documents. Though for a long time the system of decent life rights ruled the traditional fields, nowadays it is difficult to imagine the decent life rights of a modern person without digital trends and information society. For this, first of all, people should have unhindered access to the Internet. In the article, the content, theoretical elements and principles of Internet accessibility of the relative rights to a decent life were analyzed in detail by the authors, researches on digital rights were conducted. At the same time, the ideas that Internet access should be recognized as a universal right because it offers a meaningful accountability and influence channel in the global sphere, that it is an integral element of the system of modern human rights to a decent life, that free Internet access should be considered a human right, and that Internet access should be guaranteed to ensure access to open information have been put forward.